Determinants of Marketed Surplus of Milk: A Micro Level Study in Khasi Hills Region of Meghalaya - Das, Mridupaban; Singh, Ram; Feroze, S.M.; Singh, S. Basanta (Indian Journal of Extension Education, 2020)
Dairy sector has been playing a pivotal role in India’s socio-economic development by providing employment and income generating opportunities in the rural areas. At the micro level, it provides livelihood to millions of households. Animal husbandry has multi-dimensional role in improving socio-economic condition of agrarian community. In North eastern states the development of livestock sector is very slow which reflects the less production and consumption of milk. The study investigates the production, consumption, disposal and factors determining marketed surplus of milk in the state of Meghalaya. There lie opportunities for value addition and formation of dairy cooperative or farmer’s producer organization (FPO) for development of dairy sector in the state of Meghalaya.
Keywords: Correlation; Dairy; Determinant; Marketed; Surplus